Un plomb inscrit de Saint-Couat-d’Aude (Aude) : des pérégrins sur le territoire de Narbonne - Julien Aliquot; Michel Feugère (Gallia)
A fragment of an opisthographic lead plate was discovered in the sixties on the site of a Gallo-Roman villa at Saint-Couat-d’Aude (Aude), about thirty kilometres west of Narbonne. The object, which remained unpublished until now, was inscribed several times in Latin. Its most recent and best-preserved text is a two-column accounting list, combining a series of male anthroponyms with an abbreviated term beginning with a P (most likely for the word pondus) and presenting numerical indications. The inscription was carved by one person in a crude script that combines capital letters with forms borrowed from the Old Roman cursive (or capital letter cursive) used throughout the Empire between the end of the 1st c. BC and the middle of the 3rd c. AD. Eight personal names are legible or can be reconstructed with some plausibility. As far as can be judged from the right half of the inscribed fragment, they do not fit into any known onomastic formulae involving the tria nomina of Roman citizens. Moreover, these individual names are not followed by any expression indicating dependence on any other individuals. Thus, they likely refer to indigenous incolae of peregrine status, i.e. free men originating from the Narbonne colony territory. These men were allowed to live alongside the coloni and their descendants, but who were not Roman citizens and who were consequently excluded from both the local plebs and the curia. Four names, Crescens, Modestus, Successus and Tertius, are very common Latin cognomina. All of them are well known in Narbonne and its surrounding region as proper cognomina, either for Roman citizens or for slaves or freedmen. The other four names, Ambillus, Cadurcus, Matugenus and Neuto, likely belong to Celtic onomastics, which are far less common in the city’s inscriptions. The exact role of the individuals whose names are declined in the dative case is difficult to determine. They could be suppliers, as well as debtors or creditors of the estate attached to the villa. Moreover, it is not clear whether their activity was related to trade, crafts, agriculture or animal husbandry. Despite these uncertainties, the list from Saint-Couat-d’Aude enriches the epigraphic corpus of the Roman colony of Narbo Martius. This document testifies to the role of writing in daily life, as well as to the development of private accounting practices in rural areas, and it enhances the available documentation pertaining to the villae scattered throughout the Narbonne hinterland. The inscription’s most original contribution is in providing new information on the indigenous incolae of peregrine status, a category of the regional population heretofore poorly represented in epigraphic sources, and during a period prior to their integration into the civic body of the colony in the early Empire.